KONSEP WAKAF DALAM TRANSAKSI HUKUM EKONOMI SYARI’AH MENURUT PEMIKIRAN M.ABDUL MANNAN - haqiqiah, nailatus sa'adah; Yunus, Ayi (Universitas Muhammadiyah Surabaya, 2022)
Â M. Abdul Mannan is a Muslim thinker who was born in 1938, he is one of the economic thinkers in the contemporary era. His intelligence in criticizing the thoughts of various economic figures associated with Islamic law such as waqf, determines the basic economic function, which consists of consumption, production and distribution. As a scientist and academic, one of his most popular works is Islamic Economics: Theory and Practice. So from his prowess in economic thought, this paper will describe some of M.Abdul Mannan's thoughts related to economic problems, especially in the field of waqf transactions. This writing uses a descriptive method using library research, namely literature review from several book sources as well as other scientific journals. Through this paper, it can be seen some of the thoughts of M. Abdul Mannan. The conclusions drawn from this paper are the basic economic function applied by Abdul Mannan based on Islamic law which rejects antisocial and there are several operational steps, and the waqf sector Abdul Mannan said that cash waqf is better to involve Islamic banks as organizers because it is felt to managed in a transparent and accountable manner